Flowering and Rooting of Bambusa tulda Culm Cuttings in Response to Growth Regulating Substances - Kumar, Adarsh; Dhawan, Meena; Gupta, B. B. (Indian Forester, 1990)
About one year old culm cuttings of Bambusa tulda were treated with different auxinic and non-auxinic substances, planted in the month of November, 1986, and uprooted after 180 days of planting. The cuttings treated with NAA and Coumarin as well as distilled water (Control) responded to flower development, but those treated with boric acid did not show any indication of flowering. None of the cuttings responded to rooting. However, an enhancement in the flower production was discernible under different treatments as compared to control. The August planted cuttings did not produce any flowering but rooted, sprouted, and showed rhizomegenesis as reported earlier, whereas the production of flowering in November planted culm cuttings, as well as in mother clumps showed that the entire mother clump reached the induced state spontaneously between August and November.